1999
DOI: 10.1046/j.1365-2133.1999.02709.x
|View full text |Cite
|
Sign up to set email alerts
|

The naevus count on the arms as a predictor of the number of melanocytic naevi on the whole body

Abstract: A study of melanocytic naevi was carried out in southern Spain to examine the relationship between numbers of naevi at different body sites as predictors of whole-body naevus count and to determine whether the naevus count on the arms is valid for identifying the risk factors for total naevi. Subjects were the control group from a case-control study on risk factors for cutaneous melanoma. They were selected from visitors to the University of Granada Hospital (southern Spain) between 1989 and 1993. Of 200 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 26 publications
3
45
1
2
Order By: Relevance
“…The demographic profile of the studied population reflects a Caucasian skin phenotype at significant risk of melanoma with a high prevalence of Fitzpatrick skin phototype I and II and a median age of 47 years, which is not far from the mean age of diagnosis of melanoma. Our analyses confirmed that arm naevus count is, in fact, more strongly correlated to TBNC as previously described . Byles et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The demographic profile of the studied population reflects a Caucasian skin phenotype at significant risk of melanoma with a high prevalence of Fitzpatrick skin phototype I and II and a median age of 47 years, which is not far from the mean age of diagnosis of melanoma. Our analyses confirmed that arm naevus count is, in fact, more strongly correlated to TBNC as previously described . Byles et al .…”
Section: Discussionsupporting
confidence: 92%
“…found a correlation of 0·71 between the left arm and the TBNC in 131 Australian subjects. Fariñas‐Alvarez et al . suggested that the best body site in women for predicting TBNC was the leg.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heterogeneity in defining and collecting information on number of nevi across studies, our primary analysis was based on nevus counts restricted to the arms as this was the measure collected by the greatest number of studies. Nevus counts on the arms have been shown to be reliable predictors of whole-body nevus counts 44, 45. The studies contributing to the summary estimates were vulnerable to various types of bias.…”
Section: Discussionmentioning
confidence: 99%
“…Intense sunburns (experienced blistering) were separately recorded. The mole count on the left forearm was chosen, because there is evidence suggesting that the number of moles present on one part of the body fairly accurately estimates the total number of moles on the whole body (Farinas-Alvarez et al, 1999). Regular use of sun protection measures (sunscreens, hats, T-shirts, and sunglasses) and demographic variables (age, sex, and residence) were also collected.…”
Section: Methodsmentioning
confidence: 99%